2010
DOI: 10.1299/jpes.4.315
|View full text |Cite
|
Sign up to set email alerts
|

Void Fraction in a Four by Four Rod Bundle under a Stagnant Condition

Abstract: In the case of a hypothetical failure of a residual heat removal (RHR) systems under mid-loop operation, vapor generated in a reactor core forms two-phase flow in a stagnant liquid and rises the water level in the core. The vapor flows into a steam generator through a hot leg, and condenses in the steam generator. Since the flow rate of vapor from the reactor core to the hot leg depends on the water level and the void fraction α in the reactor core, the reliable analysis of the RHR failure cannot be carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Anklam and Miller [4] measured volume-averaged void fractions in an 8 × 8 rod bundle using pressure transducers. Kamei et al [5] measured volume-averaged void fractions in a 4 × 4 rod bundle under a stagnant condition using pressure transducers. Morooka et al [6] measured area-averaged void fractions in subchannels (subchannel void fractions) using an X-ray scanner system.…”
Section: Introductionmentioning
confidence: 99%
“…Anklam and Miller [4] measured volume-averaged void fractions in an 8 × 8 rod bundle using pressure transducers. Kamei et al [5] measured volume-averaged void fractions in a 4 × 4 rod bundle under a stagnant condition using pressure transducers. Morooka et al [6] measured area-averaged void fractions in subchannels (subchannel void fractions) using an X-ray scanner system.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the two-phase mixture level swell, researchers have conducted two-phase flow experiments in stagnant water (Osakabe et al, 1984;Suzuki and Murase, 1986;Kataoka et al, 1987;Kamei et al, 2010;Chen et al, 2012). Boiling experiments also have been conducted to evaluate the void fraction and actual water level during boil-off condition when water level drops due to evaporation (Shires et al, 1980;Seedy and Muralidoran, 1982;Anklam and Miller, 1983;Kumamaru et al, 1994;Qazi et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, experiments and measurements on multiphase turbulent flow in pipes or rod bundles have been conducted, and numerous fluid properties have been studied. In recent years, various simulations have been conducted in various papers [1][2][3][4][5]. Numerical analysis of subcooled two-phase flow at high pressure has confirmed that the Eulerian multiphase model including a Reynolds stress turbulence model is suitable for predicting the actual phenomenon [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%